Enhanced Regeneration and Hepatoprotective Effects of Interleukin 22 Fusion Protein on a Predamaged Liver Undergoing Partial Hepatectomy - Heng Zhou; Guomin Xie; Yudi Mao; Ke Zhou; Ruixue Ren; Qihong Zhao; Hua Wang; Shi Yin (Journal of Immunology Research)
Liver ischemia-reperfusion injury (IRI) and regeneration deficiency are two major challenges for surgery patients with chronic liver disease. As a survival factor for hepatocytes, interleukin 22 (IL-22) plays an important role in hepatoprotection and the promotion of regeneration after hepatectomy. In this study, we aim to investigate the roles of an interleukin 22 fusion protein (IL-22-FP) in mice with a predamaged liver after a two-third partial hepatectomy (PHx). Predamaged livers in mice were induced by concanavalin A (ConA)/carbon tetrachloride (CCl4) following PHx with or without IL-22-FP treatment. A hepatic IRI mouse model was also used to determine the hepatoprotective effects of IL-22-FP. In the ConA/CCl4 model, IL-22-FP treatment alleviated liver injury and accelerated hepatocyte proliferation. Administration of IL-22-FP activated the hepatic signal transducer and activator of transcription 3 (STAT3) and upregulated the expression of many mitogenic proteins. IL-22-FP treatment prior to IRI effectively reduced liver damage through decreased aminotransferase and improved liver histology. In conclusion, IL-22-FP promotes liver regeneration in mice with predamaged livers following PHx and alleviates IRI-induced liver injury. Our study suggests that IL-22-FP may represent a promising therapeutic drug against regeneration deficiency and liver IRI in patients who have undergone PHx.